Monocyte and haematopoietic progenitor reprogramming as common mechanism underlying chronic inflammatory and cardiovascular diseases. (24th October 2017) - Hoogeveen, Renate M; Nahrendorf, Matthias; Riksen, Niels P; Netea, Mihai G; de Winther, Menno P J; Lutgens, Esther; Nordestgaard, Børge G; Neidhart, Michel; Stroes, Erik S G; Catapano, Alberico L; Bekkering, Siroon
Abstract: A large number of cardiovascular events are not prevented by current therapeutic regimens. In search for additional, innovative strategies, immune cells have been recognized as key players contributing to atherosclerotic plaque progression and destabilization. Particularly the role of innate immune cells is of major interest, following the recent paradigm shift that innate immunity, long considered to be incapable of learning, does exhibit immunological memory mediated via epigenetic reprogramming. Compelling evidence shows that atherosclerotic risk factors promote immune cell migration by pre-activation of circulating innate immune cells. Innate immune cell activation via metabolic and epigenetic reprogramming perpetuates a systemic low-grade inflammatory state in cardiovascular disease (CVD) that is also common in other chronic inflammatory disorders. This opens a new therapeutic area in which metabolic or epigenetic modulation of innate immune cells may result in decreased systemic chronic inflammation, alleviating CVD, and its co-morbidities.